Higher mode effects for mid-rise buildings in relation to far fault ground motion characteristics - Durucan, Cengizhan (Elsevier Science Inc, 2022)
In this research study, activation of higher modes as functions of several ground motion parameters is studied. For this purpose, MDOF reinforced concrete shear frame with 20 storey are modeled to represent medium height buildings. Then, fast nonlinear time history analyses of the MDOF shear frame are conducted to observe the effects of the selected parameters on the activation rates of higher modes. The parameters used as ground motion characteristics are the PGA/PGV and PGD/PGV ratios of ground motion records. These parameters are known to control the length of the acceleration and displacement sensitive regions of a response spectrum, respectively. Effect of these parameters on the activation of higher structural modes are considered for ordinary far fault ground motion records without pulse like characteristics. The differences obtained in terms of the maximum inter-story drift ratio and shear force distribution along the height of the building are presented quantitatively to give detail about the effectiveness of the higher modes as a function of ground motion characteristic. The an-alyses results revealed that the effect of higher modes vary significantly in relation to considered ground motion characteristics.
Keywords: Far fault ground motion; Shear frame; Peak ground motion parameters